∫ 0 4 π tan x 1 − tan x d x
If the value of above integral can be expressed as π ( cos ϕ 1 + cos ϕ 2 − cos ϕ 3 ) , where ϕ 1 , ϕ 2 , ϕ 3 ∈ [ 0 , π ) . Find the value of ϕ 1 + ϕ 2 + ϕ 3 , and give your answer in degree.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
The quadratic equation z 2 − 2 ( 1 + 2 i ) z + 1 = 0 has zeros λ ± = 1 + 2 i ± 2 4 5 e 8 3 π i , where ∣ λ + ∣ > 1 > ∣ λ − ∣ , and hence ∫ 0 2 π cos θ − 1 − 2 i d θ = ∫ ∣ z ∣ = 1 z + z − 1 − 2 ( 1 + 2 i ) 2 i z d z = i 2 ∫ ∣ z ∣ = 1 z 2 − 2 ( 1 + 2 i ) z + 1 d z = λ − − λ + 4 π = − 2 4 1 π e − 8 3 π i by standard Residue Calculus tricks. Thus, with the substitutions u = tan x , u = sin 2 θ , followed by a move to double angles, partial fractions and finally the above result, we obtain that ∫ 0 4 1 π tan x ( 1 − tan x ) d x = ∫ 0 1 1 + u 2 u ( 1 − u ) d u = ∫ 0 2 1 π 1 + sin 4 θ 2 sin 2 θ cos 2 θ d θ = 2 ∫ 0 2 1 π ( 1 + sin 4 θ 1 + sin 2 θ − 1 ) d θ = 4 ∫ 0 2 1 π 4 + ( 1 − cos 2 θ ) 2 3 − cos 2 θ d θ − π = 2 ∫ 0 π 4 + ( 1 − cos θ ) 2 3 − cos θ d θ − π = ∫ 0 2 π 4 + ( 1 − cos θ ) 2 3 − cos θ d θ − π = − 2 1 ( 1 + i ) ∫ 0 2 π cos θ − 1 − 2 i d θ − 2 1 ( 1 − i ) ∫ 0 2 π cos θ − 1 + 2 i d θ − π = − R e [ ( 1 + i ) ∫ 0 2 π cos θ − 1 − 2 i d θ ] − π = R e [ 2 e 4 π i 2 4 1 π e − 8 3 π i ] − π = 2 4 1 π cos 8 1 π − π = π ( 2 1 + 2 1 − 1 ) which makes ϕ 1 + ϕ 2 + ϕ 3 = 6 0 + 4 5 + 0 = 1 0 5 .